2019
DOI: 10.1111/jcpe.13039
|View full text |Cite
|
Sign up to set email alerts
|

Is there an association between depression and periodontitis? A birth cohort study

Abstract: Aim To investigate the association between depression and periodontitis among adults enrolled in the 1982 Pelotas Birth Cohort, Brazil. Materials and methods Major depressive episode (MDE) and severity of depressive symptoms obtained in 2012 were considered the exposure of this study. In 2013, periodontitis, the outcome of interest, was clinically assessed and two different case definitions were used: the CDC/AAP and a combination of clinical attachment loss (CAL) and bleeding on probing (BOP) simultaneously. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 40 publications
0
44
0
6
Order By: Relevance
“…Depression prevalence is two to three times higher in patients with DM, with some cases remaining underdiagnosed [76]. Depression is also a risk factor for PD [77][78][79]. This is the reason some future research must be done to minimize the influence of this confounding factor and evaluate its strength using different questionnaires [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…Depression prevalence is two to three times higher in patients with DM, with some cases remaining underdiagnosed [76]. Depression is also a risk factor for PD [77][78][79]. This is the reason some future research must be done to minimize the influence of this confounding factor and evaluate its strength using different questionnaires [80,81].…”
Section: Discussionmentioning
confidence: 99%
“…The second hypothesis to specify the model stated that a higher level of depressive symptomatology would be a predictor of loss of OHRQoL [16], clinical attachment loss [8,9,11], poor oral hygiene habits [13], and increased proinflammatory immune response [1,2]. The hypothesis was fulfilled very partially.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with participants from Brazil, Australia and Denmark, it is concluded that depressive symptomatology is a risk factor with a small effect size on periodontal disease [8]. In another study conducted in Japan, it is pointed out that depressive disorders are related to a decrease in oral health care consultations and an increased risk of periodontal disease and tooth loss; In addition, early onset mental disorders increase the probability of suffering from oral diseases over time [9].…”
Section: Depression and Periodontal Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…An excellent example of this is the LPS from Porphyromonas gingivalis (PG-LPS), a weak TLR4 agonist, with a pentaacyl lipid A, less endotoxic properties compared to EC-LPS that induces the expression of TNF-α, IL-1β, and MIP-2, but not IL-12 p40 and IFN-γ [13], but with significant relevance in the inflammatory response in periodontal disease. Recently, inflammation derived from periodontitis has been related to the neuroinflammation state in neurodegenerative [15] and psychiatric diseases [16,17]. Oral infection with P. gingivalis in mice can produce an impairment of learning and memory abilities by the release of proinflammatory cytokines in the brain [18], as well as depression-like behavior and a reduction of brainderived neurotrophic factor (BDNF ) [19].…”
Section: Introductionmentioning
confidence: 99%